PENGARUH FINANCIAL LEVERAGE, LIKUIDITAS, UKURAN PERUSAHAAN, DAN ARUS KAS BEBAS TERHADAP KINERJA KEUANGAN PADA MASA PANDEMI COVID 19 (Studi empiris pada Perusahaan Sektor Infrastruktur, Utilitas, dan Transportasi yang Terdaftar di Bursa Efek Indonesia periode 2020 – 2021) - Muhammad Faizal Muttaqin; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of financial leverage, liquidity, firm size, and free cash flow on financial performance. The independent variables in this study are financial leverage, liquidity, firm size, and free cash flow. The dependent variable in this study is financial performance.This study uses secondary data obtained from annual reports and financial statements of companies in the infrastructure, utilities, and transportation sectors on the Indonesia Stock Exchange. The method of determining the sample using purposive sampling method. The sample used is the infrastructure, utility, and transportation sector companies listed on the Indonesia Stock Exchange from 2020 - 2021 based on predetermined criteria. The number of samples used is 126 samples. The analytical method used in this study is multiple regression analysis using the IBM SPSS 26 program.The results of this study indicate that financial leverage has a negative effect on financial performance, while liquidity does not significantly affect financial performance. The results of further research indicate that firm size and free cash flow have a positive effect on financial performance.